Clinical utility of hand held, non invasive transcutaneous bilirubinometer in neonatal jaundice: a prospective observational study - Mishra, Bibhudatta; Mishra, Bishwajit; Malini, Guruveera Jeyasingh; Mohapatra, Arjit; Biswal, Prafulla Kumar; Sinha, Shalini; Saha, Subodh; Sakhare, Wrunda; Patel, Sanjeevani (International Journal of Contemporary Pediatrics, 2021)
Background: Neonatal Jaundice is the most common morbidity in the first week of life, occurring in 60% of term and 80% of preterm newborn. However, visual inspection, being subjective, usually inaccurate and unreliable and will result in a number of unnecessary blood sampling. Taking all these in to considerations, transcutaneous bilirubinometer (TCB) may provide a solution which is an objective, noninvasive, fast and painless method of bilirubin estimation. Methods: Transcutaneous bilirubinometer levels were measured at forehead and sternum and blood samples for TSB were collected by venepuncture within 30 minutes and sent to biochemistry lab. After getting serum bilirubin reports, TCB and TSB values were compared by using Bhutani’s hour specific nomogram. Results: The correlation between serum bilirubin and transcutaneous bilirubin measured at forehead and sternum is very good at serum bilirubin <15 mg/dl, r value (Karl Pearson’s Correlation co-efficient) is 0.93 and 0.94 respectively. Conclusions: The findings of the present study indicate that the TCB is a reliable screening tool for hyperbilirubinemia in newborns >35 weeks of gestation, especially with bilirubin levels ≤15 mg/dl in 2-7 days of life. TCB can be a viable option for universal screening. Incorporating the use of TCB devices in clinical practice, can reduce the need for blood sampling for the management of neonatal jaundice.